Proficiency Skill Development Kit - California State Dept. of Education, Sacramento. Office of Program Evaluation and Research; California State Dept. of Education, Sacramento. Office of Program Evaluation and Research ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
This manual was developed to aid local school districts in complying with the requirement of California's Pupil Proficiency Law that districts provide extra help to students not making adequate progress towards basic skill mastery. Guidelines for the development of instructional packages keyed to the school districts proficiency tests, various content areas and grade levels, and which focus on personalized instruction in specific skills, are provided. The kit models a product, and thus, aims to develop the knowledge and skills teachers will need to design similar materials for their own students. An introductory section details the kit's purpose and how it works. Following sections outline procedures for meeting the kit's objectives: writing instructional objectives; incorporating materials already available to the teacher into the kit; developing learning activities keyed to objectives and learner characteristics; developing assessments and other kit components; managing the materials in the classroom. Teacher pretests and posttests are incorporated for each objective. The final section briefly suggest ways of obtaining the most effective use of materials in the classroom. Appendixes include information on resources, a sample kit in the form of Los Angeles Unified School Districts' Competency Achievement Packet, and answer keys to pretests and posttests. (Author/AEF)
Availability: Publication Sales, California State Department of Education, P.O. Box 271, Sacramento, CA 95802 ($7.50).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Basic Skills; Classroom Techniques; Criterion Referenced Tests; Curriculum Development; Elementary Secondary Education; Material Development; Mathematics; Pretests Posttests; Reading Skills; Skill Development; Writing Skills; Pupil Proficiency Law (California); Guides, Classroom -- Teacher